The moderating role of emotional intelligence in the link between self-esteem and symptoms of eating disorders. - Peláez-Fernández, María Ángeles; Romero Mesa, Juana; Franco-Paredes, Karina; Extremera-Pacheco, Natalio (Wiley, 2022)
Objective: This research aimed to explore the moderating role of emotional intelligence (EI) in the relationship between self-esteem and eating disorders (ED) symptomatology. Method: A battery of online questionnaires was administered to a sample of 516 adults including university students and a community population. The sample, age range of 18–77 years (X=38.90; SD=14.76), was made up of 63% women and32% men. Results: EI moderated the association between self-esteem and ED symptomatology for the total sample. However, a gender-specific analysis showed that the moderation effect was only significant for women. Specifically, when women reported a low level of self-esteem, those with high scores in EI reported lower scores in ED symptoms than those with low EI. Discussion: Our findings are discussed in terms of the need for future research to understand the different gender associations and to consider these differences in further intervention programs for reducing the risk of ED, in which training in emotional skills may be more beneficial for women than men.
This study provides preliminary (and correlational rather than causal) evidence on the potential importance of emotional skills in understanding ED symptoms
Keywords: Nutrición - Trastornos; Autoestima; Inteligencia; Emociones; Eating disorders; Emotional intelligence; Moderation; Self-esteem